2009
DOI: 10.1017/s1368980009990255
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition and health education intervention for student volunteers: topic-wise assessment of impact using a non-parametric test

Abstract: Objective: To assess the impact of a classroom-based nutrition and health education intervention among student community volunteers in improving their knowledge on individual topics. Design: Prospective follow-up study. Topic-wise knowledge change among student volunteers on individual topics (twenty-one questions related to nutrition and health, eight questions related to infectious diseases and two questions related to obesity and hypertension) pertaining to nutrition and health was evaluated at baseline and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 18 publications
1
27
0
3
Order By: Relevance
“…Bullen and Benton [39] concluded that while participants may gain factual knowledge, they do not develop the skills to bring about behavioural change. Despite this, the importance of popularizing nutrition knowledge is essential, and it is widely acknowledged that gaining accurate relevant knowledge is the basis for behavioural changes [40][41][42]. Our study found, for example, that an awareness that vegetables and fruits are richer in vitamin C was strongly related to the behaviour of consuming vegetables at least once per day.…”
Section: Discussionmentioning
confidence: 56%
“…Bullen and Benton [39] concluded that while participants may gain factual knowledge, they do not develop the skills to bring about behavioural change. Despite this, the importance of popularizing nutrition knowledge is essential, and it is widely acknowledged that gaining accurate relevant knowledge is the basis for behavioural changes [40][41][42]. Our study found, for example, that an awareness that vegetables and fruits are richer in vitamin C was strongly related to the behaviour of consuming vegetables at least once per day.…”
Section: Discussionmentioning
confidence: 56%
“…Vijayapushpam et al (51) To assess the impact of a classroom-based nutrition and health education intervention among student community volunteers in improving their knowledge on individual topics 687 undergraduate student volunteers…”
Section: Rct 2 Weeksmentioning
confidence: 99%
“…A treatment effect was found for the nutrition education and garden group for: ability to identify vegetables; willingness to taste capsicum, broccoli, tomato and pea; and student preference to eat broccoli and pea as a snack HPS, health-promoting school; CT, controlled trial; RCT, randomized controlled trial; PSE, Personal and Social Education; SES, socio-economic status. Radcliffe et al (36) Wind et al (37) Parker and Fox (38) Rana and Alvaro (39) McVey et al (45) Laurence et al (46) O'Brien et al (47) Overall rating* Mullally et al (44) Young (40) Ellis and Ellis (42) Vereecken et al (43) Overall rating* (48) Bullen and Benton (49) Kreisel (50) Vijayapushpam et al (51) Hamilton-Ekeke and Thomas (52) Morgan et al (53) Overall Nutrition promotion using health-promoting schools approach: systematic review Table 2 Continued…”
Section: Before and Aftermentioning
confidence: 99%
See 1 more Smart Citation
“…Higgins et al, 2010 (42) Descrever práticas de bem estar em estudantes universitários, desenvolver um curso de educação em boas práticas de saúde e avaliar o impacto do curso sobre a prática e o aprendizado dos alunos.…”
unclassified